Thromboembolic complications in children with COVID-19 and MIS-C: A narrative review - Trapani, Sandra; Rubino, Chiara; Lasagni, Donatella; Pegoraro, Francesco; Resti, Massimo; Simonini, Gabriele; Indolfi, Giuseppe (Frontiers in Pediatrics, 2022)
COVID-19 and multisystem inflammatory syndrome in children (MIS-C) have been associated with a higher incidence of hypercoagulability and thromboembolic events (TEs), even in children, leading to relevant morbidity and mortality. However, our understanding of such complications in childhood is limited. To better understand the incidence, clinical manifestations, risk factors, and management of COVID-19 and MIS-C-related TEs in children, a review of the current literature and a brief update on pathophysiology are given. Sixty-two studies, describing 138 patients with TEs associated with COVID-19 or MIS-C, were included. The overall number of TEs was 157, as 16 patients developed multiple TEs: venous TEs represented the majority (54%), followed by arterial thrombosis (38%, mainly represented by arterial ischemic stroke-AIS), and intracardiac thrombosis (8%). Within the venous TEs group, pulmonary embolism was the most frequent, followed by deep venous thrombosis, central venous sinus thrombosis, and splanchnic venous thrombosis. Notably, 10 patients had multiple types of venous TEs, and four had both venous and arterial thrombosis including a newborn. Most of them (79 cases,57%) had at least a predisposing condition, being obesity the most frequent (21%), especially in patients with pulmonary embolism, followed by malignancy (9%). In 35% of cases, no data about outcome was available About one third of cases recovered, 12% improved at discharge or follow-up, and 6% had persistent neurological sequelae. The mortality rate was 12%, with death due to comorbidities in most cases. Most fatalities occurred in patients with arterial thrombosis. Pediatricians should be aware of this life-threatening possibility facing children with SARS-CoV-2 infection or its multisystemic inflammatory complication, who abruptly develop neurological or respiratory impairment. A prompt intensive care is essential to avoid severe sequelae or even exitus.